Impact of dietary salicylates on angiogenic factors and biochemical parameters in a rat model of preeclampsia - Joanna Suliburska; Rafsan Syabani Cholik; Marta Karaźniewicz-Łada; Dorota Wronka; Anna Karlik; Agnieszka Waśkiewicz; Katarzyna Skrypnik; Paweł Kołodziejski; Adam Cieślak; Łukasz Przybył (PLoS ONE, 2025)
Background The pathophysiology of preeclampsia involves impaired cytotrophoblastic invasion, placental ischemia, inflammation, and angiogenic imbalance. Prophylactic low-dose aspirin can reduce the risk of preeclampsia and fetal growth restriction in high-risk women. This study evaluated the effect of dietary salicylates on the development of preeclampsia in rats treated with L-NAME (NG-nitro-L-arginine-methyl ester). Methodology Pregnant Sprague-Dawley rats were randomly assigned to six groups and treated with dietary salicylates at two dose levels (1 and 10 mg/kg diet) or aspirin (doses adjusted to dietary salicylates). Preeclampsia was induced by administering L-NAME in drinking water from gestational days 6–19. Results Neither dietary salicylates nor aspirin, at either dose, affected blood pressure in L-NAME-treated rats. The lower dose of dietary salicylates significantly reduced urinary albumin levels. Both interventions prevented an increase in the sFlt/PLGF ratio and mitigated histopathological placental changes in preeclamptic rats. The higher dose of aspirin reduced placental VEGFR2 protein levels. Conclusion Dietary salicylate supplementation does not provide clear preventive effects against preeclampsia.